Vietnamese migrants in Australia and the global digital diaspora : histories of childhood, forced migration, and belonging - Nguyen Austen, Anh (Abingdon, Oxon ; New York : Routledge, 2023)
"Through oral histories, memoirs, and Facebook posts of Vietnamese adults who entered Australia as children after the Vietnam War (and Vietnamese refugees, war orphans, and children of refugees) this book provides insight into the memories of forced migrant childhoods and histories, as well as the complexities of national and transnational identity and belonging in digital diaspora. As war and displacement compounds the need for creating communities and histories for cultural continuity, this book is a history about childhood and migration for Vietnamese diaspora of refugees, adoptees, and second generation in Australia and their connectedness in global and digital diaspora. Using Facebook as a digital archive for historical research, Vietnamese in Australia and the Global Digital Diaspora presents new methods for the study of what Austen proposes as a new area of digital diaspora studies for interdisciplinary research about real and digital life in the humanities and social sciences. As a contemporary digital diaspora study of Vietnamese forced child migrants from 1975 to the present, this book contains mixed methods historical analysis of the impact of war and displacement on memories of childhood. This book presents an innovative history of the national, transnational, digital, and contemporaneous lives of Vietnamese child migrants, which will make a significant contribution to the discourse on transnational childhood, migration, and belonging for refugees and migrants in the twenty-first century"--
Introduction: Vietnamese refugeedom, ephemeral historical archives, and belonging in digital diaspora studies -- Migration and global digital diaspora -- Digital diaspora of Vietnamese refugees on Facebook -- Unaccompanied minors, transitional memories, escapes from Vietnam to Facebook -- Childhood and becoming global and digital refugees -- Histories of gratitude: Vietnamese boat children, journeys, and rescues on Facebook -- Refugee childhood: agency, self-determination, and belonging -- Complexities of real and digital belonging -- Vietnamese adoptees and the complexities of belonging on and off Facebook -- Second generation Vietnamese : civic engagement and belonging in Australia and in the digital diaspora -- Conclusion: Historical continuity for Vietnamese in the global and digital diaspora.
Keywords: Facebook (Electronic resource); Vietnamese -- Australia; Immigrant children -- Social networks -- Australia; Vietnamese -- Social networks -- Australia; Refugees -- Social networks -- Australia; Online social networks -- Australia; Internet and immigrants -- Australia; Immigrants -- Cultural assimilation -- Australia; HISTORY / Asia / Southeast Asia; HISTORY / Australia & New Zealand; HISTORY / United States / 21st Century